Robotics And Artificial Intelligence - Munjal, Sahil; Malik, Sachin; Bhardwaj, Sahil (IJRDO -Journal of Computer Science Engineering, 2015)
Robotics and Artificial Intelligence stand as two disciplines related to computer science. Robotics aims at building robots which autonomously perceive, (eventually) reason and act (e.g., communicate) in real physical environments. A.I. aims at representing knowledge and reasoning on it, in a way as close as possible to human reasoning. Without raising arbitrary barriers, these two disciplines are different: general conferences in the A.I. field include IJCAI, ECAI, AAAI, RFIA and many specialized conferences ; general conferences in the Robotics field include ICRA, IROS and many other specialized conferences, e.g., on control theory. However, many Robotics-claimed work include A.I. algorithms: The A* algorithm and its variants are used for path planning, i.e., finding a continuous path from location A to location B on a map while avoiding obstacles recorded on the map; Evolutionary computing is used to optimize online merging of maps represented as occupancy grids, or in microrobotics; many examples can be drawn along similar lines. In this paper, we sketch the main goals of A.I. and of Robotics, record their differences and highlight the convergence points, aiming at a better communication between the two communities.